2021
DOI: 10.2147/dddt.s296880
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Anticancer Strategy of Sonodynamic Therapy Combined with PI-103 Against Hepatocellular Carcinoma

Abstract: Purpose: Sonodynamic therapy (SDT) is considered a promising therapeutic strategy for the effective elimination of cancer cells. However, developing novel sonosensitizers with potentially high SDT efficacy remains a considerable challenge. Herein, we utilized near-infrared dye IR820 nanobubbles (NBs) combined with a dual PI3K/mTOR inhibitor PI-103 for the SDT treatment of hepatocellular carcinoma (HCC) in vitro. Methods: The generated reactive oxygen species (ROS) were quantified using 2,7-dichlorodihydrofluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…SDT is effective in treating a variety of tumors (Um et al, 2021). Recently, the application of SDT has been studied extensively (Wang et al, 2021), and our team also showed that SDT could promote cell apoptosis through the mitochondrial pathway in HCC cells (Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 80%
“…SDT is effective in treating a variety of tumors (Um et al, 2021). Recently, the application of SDT has been studied extensively (Wang et al, 2021), and our team also showed that SDT could promote cell apoptosis through the mitochondrial pathway in HCC cells (Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 80%
“…Meanwhile, FAM3D expression was negatively correlated with PI-103 drug sensitivity. PI-103 is a DNA-PK/PI3K/mTOR inhibitor that has been used in preclinical studies, and demonstrated anti-proliferative effects on a variety of cancer types 57 , 58 . To sum up, the results of drug sensitivity analysis could help us understand the associations between FAM3 family genes expression and numerous anticancer drugs, which provided some ideas for exploring tumor therapy and avoiding tumor drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, FAM3D expression was negatively correlated with PI-103 drug sensitivity. PI-103 is a DNA-PK/PI3K/mTOR inhibitor that has been used in preclinical studies, and demonstrated anti-proliferative effects on a variety of cancer types [53,54]. To sum up, The results of drug sensitivity analysis could help us understand the associations between FAM3 family genes expression and numerous anticancer drugs, which provided some ideas for exploring tumor therapy and avoiding tumor drug resistance.…”
Section: Discussionmentioning
confidence: 99%